Early Business Model Evolution in Science-based Ventures: The Case of Advanced Materials. Issue 3 (June 2016) - Lubik, Sarah; Garnsey, Elizabeth
Abstract : Business models of many types have received attention in recent management research, but less work has focused on models suited to the commercialization of scientific research in areas such as biotech, green tech and advanced materials. University spin-outs (USOs) are often required to demonstrate the potential value and viability of generic new technologies, but there has been little work to date looking at appropriate business models for these new firms. This study investigates how the business models of advanced material USOs often develop by trial and error in response to their unique challenges. Many of the most commonly recommended strategies and resultant models do not translate directly into practice for ventures with generic, early-stage technologies, particularly those that have to commit considerable resources and attract funds and partners early on. Case exemplars reveal business models and strategies that have been successful, and also less successful, in creating value from science-based innovations of advanced material USOs. This evidence informs our conclusions and recommendations.